AN ANALYSIS ON STUDENTS’ ERRORS IN USING DIRECT AND INDIRECT SPEECH IN SENTENCES AT SIXTH SEMESTER OF STAI HUBBULWATHAN DURI - Mohd. Rafi Riyawi; Deby Alwiyah (STAI Hubbulwathan Duri, 2017)
Based on the researchers observation, it was found that most of the students are difficult in using direct and indirect speech of statement. They are difficult to change tenses, pronoun and adverb of time from direct into indirect speech. So, the researchers were interested in carrying out the research about this problem. The objective of the research is to find out kinds of error in using direct and indirect speech and cause of the errors. The design of this research was descriptive quantitative. There is 1 class at sixth semester of STAI Hubbulwathan Duri. The Population the sixth semester of STAI Hubbulwathan Duri are 19 students. The researchers use the sixth semester class (19 students) as sample. The writer gave written test by 10 items. And then test result will be presented in the form of tables and picture to make it easier to understand. To know of steps take in conducting an error analysis, the researchers use steps classify errors and quantify errors. After analyzing the data, the researchers found kind of errors which made by the students and the cause of the errors. Berdasarkan pengamatan peneliti, ditemukan bahwa sebagian besar mahasiswa mengalamai kesulitan dalam menggunakan direct speech dan indirect speech. Mereka sulit mengubah tenses, pronoun dan adverb of time dari direct speech ke indirect speech. Peneliti tertarik untuk melakukan penelitian tentang masalah ini. Tujuan dari penelitian ini adalah untuk mengetahui jenis kesalahan dalam menggunakan ujaran langsung dan tidak langsung dan penyebab kesalahan. Rancangan penelitian ini adalah deskriptif kuantitatif. Penelitian dilakukan pada semester enam STAI Hubbulwathan Duri. Populasi semester enam STAI Hubbulwathan Duri adalah 19 orang mahasiswa. Peneliti akan menggunakan semester enam (19 siswa) sebagai sampel. Peneliti memberikan tes tertulis sebanyak 10 item. Dan kemudian hasil tes akan disajikan dalam bentuk tabel dan gambar sehingga lebih mudah dimengerti. Untuk mengetahui langkah-langkah dalam melakukan analisis kesalahan, peneliti akan menggunakan langkah-langkah untuk mengklasifikasikan kesalahan dan mengkuantifikasi kesalahan. Setelah menganalisa data, peneliti menemukan jenis kesalahan yang dilakukan oleh mahasiswa dan penyebab kesalahannya.